2018
DOI: 10.1002/suco.201700231
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of shear‐critical reinforced engineered cementitious composites members under reversed cyclic loading

Abstract: Engineered cementitious composites (ECC) possesses characteristics that make it suitable in the zones of high ductility and high‐shear demand of structural elements. In this study, a numerical modeling method for simulating shear‐critical reinforced ECC members was put forward. Uniaxial cyclic constitutive models of ECC in compression and tension were proposed, including unloading and reloading scheme. Softening phenomenon and Poisson effect of cracked ECC were also considered in the proposed 2‐dimension const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The predicted hysteresis behavior of these RECC columns agreed better with the tested curves compared with that simulated using the initial Han et al's model. Wu et al 62 further simulated the shear-critical RECC and RC/ECC short columns and shear walls under cyclic loading based on OpenSEES. The combination of nonlinear beamcolumn elements and plane-stress quadrilateral elements was applied due to the inapplicability of nonlinear beam-column elements for simulation of shear-critical members.…”
Section: Numerical Simulation Of Seismic Behavior Of Recc and Rc/ecmentioning
confidence: 99%
“…The predicted hysteresis behavior of these RECC columns agreed better with the tested curves compared with that simulated using the initial Han et al's model. Wu et al 62 further simulated the shear-critical RECC and RC/ECC short columns and shear walls under cyclic loading based on OpenSEES. The combination of nonlinear beamcolumn elements and plane-stress quadrilateral elements was applied due to the inapplicability of nonlinear beam-column elements for simulation of shear-critical members.…”
Section: Numerical Simulation Of Seismic Behavior Of Recc and Rc/ecmentioning
confidence: 99%
“…31 As known, shear failure is more brittle and catastrophic compared with flexural one in RC structures. Researches mentioned above [21][22][23][24][25][26][27][28] have proved the effectiveness of ECC on strength and toughness enhancement in member scale. However, the mechanical behavior of ECC under pure shear, especially in material scale, is not very clear so far.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Based on the excellent bridging effect, the shear 10 and compressive 20 response of ECC materials exhibit significantly improved toughness with saturated crack propagation, compared with FRC. As a result, ECC is particularly suitable for shear members, research works including beams, 21,22 columns, 23,24 joints 25,26 and couple beams 27,28 all concluded that the application of ECC brought significant improvement in strength and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al (2018) also reported that ECC jacketed columns failed in ductile modes and exhibited better plastic deformation and energy dissipation capacity. In addition to the experimental investigations, a few analytical studies (Zohrevand and Mirmiran 2010;Gencturk et al 2013;Roehm et al 2015;Wu et al 2018) were also conducted to propose concrete models considering the constitutive material properties of fiber reinforced concrete (FRC). Wu et al (2018) proposed uniaxial cyclic constitutive material models in compression and tension, followed by a numerical modeling technique to simulate short column ECC members using OpenSees (Mazzoni et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the experimental investigations, a few analytical studies (Zohrevand and Mirmiran 2010;Gencturk et al 2013;Roehm et al 2015;Wu et al 2018) were also conducted to propose concrete models considering the constitutive material properties of fiber reinforced concrete (FRC). Wu et al (2018) proposed uniaxial cyclic constitutive material models in compression and tension, followed by a numerical modeling technique to simulate short column ECC members using OpenSees (Mazzoni et al 2007). Recently, Pang et al (2019) also developed 3D nonlinear finite element models to simulate different FRC (steel fibers reinforced concrete, polypropylene fibers reinforced concrete, and steel polypropylene hybrid fiber reinforced concrete) columns.…”
Section: Introductionmentioning
confidence: 99%